An Empirical Study of Institutional Investor and Enterprise Innovation - Min, Cheng (European Scientific Journal, ESJ, 2018)
Innovation is the driving force of social and economic development, and a decisive factor in enhancing national competitiveness. In recent years, more and more countries have taken innovation to a strategic height. Chinese institutional investors have an increasing share of the overall ownership and make a remarkable improvement in the market position. Based on an increasingly significant role in the capital market, they actively intervene in the management of the enterprise, focusing on long-term improvement of corporate performance. Correspondingly, Institutional investors can also affect the level of technological innovation by participating in corporate governance. This study analyzes the mechanism of institutional investment affecting the technological innovation of enterprises, and takes an empirical test of institutional investors on the impact of technological innovation. The results show that the overall ownership of institutional investors has a significant positive impact on corporate R&D expenditure. This paper proposes that the future policies should still be oriented toward the development and support of institutional investors, and give further play to their efforts to promote technological innovation of enterprises.